Jaminan Efektivitas Pelaksanaan Pendidikan dan Pelatihan pada Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Riau - Desvi Emti; Kodarni Kodarni (Al-Manar Journal of Economic and Social Studies, 2025)
This study aims to determine the effectiveness of the implementation of education and training provided online by the Human Resources Development Agency to ASN. The types and sources of data for this study consist of primary and secondary data, namely research data obtained directly from research informants and reference data related to the research study. Data collection techniques used to collect secondary data are by using interviews and reference books and reports related to the research. The research informants numbered 10 (ten) informants who know and manage education and training at the Riau Province Human Resources Development Agency, namely 9 (nine) informants for Education and Training Managers, Widyaiswara, Members of the Riau Province Human Resources Development Agency's Quality Assurance Committee and 1 (one) informant for training alumni. The data analysis technique used qualitative data analysis. The results of the study indicate that the implementation of education and training at the Riau Province Human Resources Development Agency has been carried out sustainably, including through online learning schemes. Guaranteeing the effectiveness of the implementation of education and training at the Riau Province Human Resources Development Agency requires strengthening through an integrated and sustainable evaluation system. This strengthening is expected to ensure that training is not only oriented towards program implementation, but also provides a real contribution to improving ASN competency and the quality of organizational performance.